Family Forward: Promoting Family Adaptation Following Pediatric Acquired Brain Injury. Issue 3 (12th December 2016) - Hickey, Lyndal; Anderson, Vicki; Jordan, Brigid
ABSTRACT: This article describes a new and innovative social work intervention, Family Forward, designed to promote early adaptation of the family system after the onset of a child's acquired brain injury. Family Forward is integrated into inpatient rehabilitation services provided to the injured child and recognizes the important role of family in child rehabilitation outcomes and the parallel process of recovery for the child and family following an injury. Family Forward is informed by clinical practice, existing research in family adaptation after pediatric acquired brain injury, the resiliency model of family adjustment and adaptation, and family therapy theories and approaches.